The washback effect of TOEFL iBT and a local English Proficiency Exam on students' motivation, autonomy and language learning strategies. Issue 10 (October 2021) - Sadeghi, Karim; Ballıdağ, Aylin; Mede, Enisa
Abstract: This study aimed to investigate the washback effect of two high stakes tests, a global language proficiency test (i.e., TOEFL iBT) and a local English Proficiency Exam (developed and administered by a state university) on students' motivation and their autonomy. The study also examined whether proficiency level moderated the potential washback effect among the two groups of test takers. Additionally, the study tried to find out the language leaning strategies used by both groups and explore the reasons behind their preferences. The study was conducted with two English language preparatory programs offered at a state university in Turkey: University Preparatory Program (UPP) and Dual Degree Program (DDP). At the end of the UPP program, the students are required to take the university's proficiency test while as for the UPP, they need to take a valid TOEFL iBT. Data were collected from 152 preparatory students (N = 65 for DDP; N = 87 for UPP) whose proficiency levels were based on the CEFR Framework ranging from A2 (upper elementary) to B1 (pre-intermediate) to B2 (intermediate). In addition to the above proficiency tests, data were gathered via motivation questionnaire, autonomous learning scale and student interviews. The results revealed no washback of TOEFL iBT exam on students' motivation regardless of their proficiency level. No washback was also observed on students' autonomy except for A2 level DDP students who had higher level of autonomy than the A2 level UPP students. Finally, the two groups used more similar than different language learning strategies while practicing the four language skills. The findings afford pedagogical implications for the use of high-stakes tests in English preparatory programs. Abstract : Washback; High-stakes tests; TOEFL-iBT; English proficiency exam; Motivation; Autonomy, language learning strategies; Language testing.